LEGAL REGULATION OF COOPERATION BETWEEN STATES IN THE FIELD OF TOURISM (World Bulletin of Management and Law, 2026)
Tourism has become one of the most dynamic and rapidly developing sectors of the global economy. It significantly contributes to economic growth, employment generation, cultural exchange, and international cooperation. The development of tourism requires effective legal regulation and coordinated policies between states. International tourism involves the movement of people, capital, services, and information across national borders, which creates the need for comprehensive legal frameworks governing tourism relations. This article examines the legal regulation of cooperation between states in the field of tourism and analyzes the role of international legal instruments, bilateral and multilateral agreements, and international organizations in the regulation of tourism activities. The research also explores the importance of harmonizing national tourism legislation with international legal standards and promoting sustainable tourism development. Particular attention is given to the protection of tourists' rights, environmental sustainability, and the role of legal mechanisms in ensuring responsible tourism practices. The article concludes that strengthening international legal cooperation and improving tourism governance are essential for ensuring the sustainable development of global tourism
Keywords: international tourism law; tourism regulation; interstate cooperation